1982
DOI: 10.1161/01.res.51.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Responses of thoracic spinothalamic neurons to intracardiac injection of bradykinin in the monkey.

Abstract: SUMMARY. Bradykinin stimulates afferent fibers arising in the heart and may be involved in the mediation of anginal pain and the pain associated with myocardial infarction. The sensation of pain requires that noxious information reach the brain. The purpose of the present study was to determine whether the spinothalamic tract is involved in transmitting noxious information from the heart to the brain. Bradykinin was injected (0.3-3.5 jug/kg) into the heart via a catheter in the left atrium while we recorded fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(26 citation statements)
references
References 36 publications
0
23
2
1
Order By: Relevance
“…34,41 Bradykinin when applied to the cardiac surface produces a significant increase in cardiac afferent nerve activity including activation of spinothalamic tract neurons. 42,43 Application of bradykinin, as part of a mixture of agents, to the surface of the heart elicits a pseudoaffective response in rats suggestive of pain; 44 however, when infused intracoronary into conscious dogs, Pagani et al observed hemodynamic effects but no evidence of pain. 45 Gutterman et al 46 also showed that the afferent neural response to epicardial application of bradykinin is an increase in afferent nerve activity, but the pattern of the increased activity differed from that observed during brief periods of myocardial ischemia, suggesting that bradykinin release does not fully explain cardiac pain sensation.…”
Section: Mechanism Of Cardiac Painmentioning
confidence: 99%
“…34,41 Bradykinin when applied to the cardiac surface produces a significant increase in cardiac afferent nerve activity including activation of spinothalamic tract neurons. 42,43 Application of bradykinin, as part of a mixture of agents, to the surface of the heart elicits a pseudoaffective response in rats suggestive of pain; 44 however, when infused intracoronary into conscious dogs, Pagani et al observed hemodynamic effects but no evidence of pain. 45 Gutterman et al 46 also showed that the afferent neural response to epicardial application of bradykinin is an increase in afferent nerve activity, but the pattern of the increased activity differed from that observed during brief periods of myocardial ischemia, suggesting that bradykinin release does not fully explain cardiac pain sensation.…”
Section: Mechanism Of Cardiac Painmentioning
confidence: 99%
“…Physiological and pharmacological studies show that BK activates cardiac nociceptors and sympathoexcitatory responses via kinin B2 receptors located in thinly myelinated A␦ and unmyelinated C-fiber afferent endings in the heart (1,23,39,40). The afferent fibers transmitting the action potentials enter the upper thoracic spinal cord where spinal neurons, spinothalamic tract cells, spinoreticular tract, and other ascending pathway neurons process this information (2)(3)(4)(5)(6)27). However, the signaling mechanisms involved in detection of myocardial ischemia and activation of cardiac sympathetic or spinal afferent nerve endings are not fully known.…”
mentioning
confidence: 99%
“…Thus, a possible contribution of chemical substances released by coronary occlusion to excite the cardiac afferents cannot be excluded from the present study. Previous studies also suggested that the sympathetic afferent nerves may transmit the sensation of pain during myocardial ischemia to the central nervous system (WHITE, 1957;BAKER et a!.,1980;BLAIR et a!., 1982). Thus, further experiments are required to evaluate the net autonomic response to cardiogenic hypotension determining the central interactions of input from cardiac sympathetic afferents and from arterial baroreceptors and cardiac vagal afferents, and to determine more exact interaction with impaired cardiac function and cardiac sympathetic afferents during the hypotension induced by coronary occlusion.…”
Section: Discussionmentioning
confidence: 99%